Annual report 2021: CGIAR Research Program on Policies, Institutions, and Markets - CGIAR Research Program on Policies, Institutions, and Markets (CGIAR Research Program on Policies, Institutions, and Markets, 2022)
PIM had a productive final year centered on synthesizing findings while continuing to respond to demand on the impacts of COVID-19 and preparing the transition to the new CGIAR portfolio. PIM findings and engagement contributed to Myanmar’s response to COVID-19, South Africa’s policies on resilience to climate change, Tunisia's policies for pastoral development, a reform of Nigeria’s national agricultural research system, Ghana’s fish seed and farm certification system, gender strategies for three agricultural value chains in Honduras, and genome editing guidelines for the agricultural sector in four African countries. PIM research informed policy documents of FAO, IFAD, One CGIAR, the UK Government, the World Bank and the World Food Programme. PIM tools enabled more equitable co-management of 76 protected areas in Peru and informed World Bank social protection projects. Books on food security in Bangladesh and Malawi, trade in Latin America, African agricultural value chains and gender were published. 42 PIM synthesis briefs and notes were issued, summarizing research results in key thematic areas. PIM contributed 181 journal articles, 8 journal issues (on demand driven seed systems, China’s response to COVID-19, agriculture and food security in China under COVID-19, food loss and waste, landscape restoration, multistakeholder fora in forestry and two issues on gender), 15 book chapters and about 500 non-peer-reviewed outputs. 16 PIM webinars were organized. PIM’s contributions to the United Nations Food Systems Summit covered agricultural extension, food system innovations and digital technologies, the future of small farms, the science-policy interface, the cost of ending hunger by 2030, food waste and loss, management of the commons and gender. Building on past PIM investments in economywide modeling tools and social accounting matrices, PIM teams continued to assess the impacts of COVID-19 and policy responses at country level. Lessons learned from PIM country-level analyses on COVID-19’s impacts on food systems, poverty and diets are summarized in a chapter of the IFPRI 2022 book “COVID19 and global food security: Two years later”. A paper in partnership with the CGIAR COVID19 Hub reviewed the literature on agri-food value chains for evidence of fractures and resilience in response to the pandemic. The results of coordinated studies on the impacts of COVID-19 on value chains in different countries were published. Several cross-CGIAR outputs initiated by PIM speak to the fulfillment of PIM’s convening role as an integrating program: the CGIAR Foresight Report and CGIAR foresight website; several outputs produced through the CGIAR Community of Excellence on Seed Systems Development, and the CGIAR book “Advancing gender equality through agricultural and environmental research: Past, present, and future” are examples. Other examples of PIM global public goods produced in 2021 are 27 innovations at various stages of uptake, a cross-cutting effort to distill PIM lessons on migration; new or updated social accounting matrices for 25 countries; and lessons and tools on stakeholder platforms for natural resource governance. Independent reviews assessed the effectiveness of PIM’s partnerships and the use by partners of PIM’s work on economywide modelling, agricultural insurance, tenure and governance, and the Ag-Incentives database.